Current situation and development trend of line selection method for single-phase grounding fault in mine power supply system - Zhanshe YANG; Cheng ZHANG; Xiang RONG (Meikuang Anquan)
The mine power supply system usually adopts the neutral point ungrounded mode or the arc suppression coil grounded mode, due to the particularity and complexity of underground environment, the problem of single-phase grounding fault line selection has not been well solved. This paper analyzes and compares the advantages and disadvantages of the two grounding methods and the difficulty of line selection when single-phase grounding fault occurs in the system. This study introduces the active line selection method, passive line selection method (including the line selection method based on steady state information and the line selection method based on transient information) and the intelligent algorithm fusion line selection when the single phase grounding fault occurs in the mine power supply system. The active line selection method mainly detects the fault line by detecting the injected signal. The passive line selection rule is based on the steady state information and transient information after the fault occurs. Intelligent algorithm fusion line selection can make full use of fault characteristics and has a broad development prospect. In view of the problems such as no disturbance identification, poor reliability of single fault line selection method, obvious advantages of intelligent algorithm fusion line selection but not well applied, the development trend of fault line selection method of mine power supply system is proposed.